Activist translation of queer graphic novels: The case of Heartstopper in Turkey - Alan, Cihan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
In the context of a significant deterioration of LGBTQI+ rights in Turkey, the translation of the queer graphic novel, Heartstopper, into Turkish (as Kalp Çarp?nt?s?) was labelled “harmful for children” by the Board of Protecting Minors from Obscene Publication, a state mechanism that controls publications for children. The precarity of queer translation in the Turkish publishing industry raises the question of the potential for activist translation to disrupt anti-LGBTQI+ hegemonic discourses and their silencing of LGBTQI+ youth sexuality and identity in repressive contexts. The study on which this article is based investigated the performativity of Kalp Çarp?nt?s? as a translation and focused on the practices of translation agents who were involved in the translation, publication, and reception of Heartstopper in Turkey. It provides a qualitative analysis of Ömer Anlatan’s engagement with the graphic novel and its portrayal of LGBTQI+ youth, a semi-structured interview with the translator and an account of the reviews of the book. The study reveals the translator’s multimodal interventions in the text, driven by his professional background as a counsellor and his knowledge of the language used by the LGBTQI+ community in Turkey. It accounts for the unwavering support of the publisher despite public controversies and also for the timely sociopolitical impact of the translation in and beyond LGBTQI+ circles in Turkey. The compelling case of the Turkish translation of Heartstopper as a queer graphic novel reminds us that the solidarity of multiple agents is crucial in paving the way towards social and queer justice for children and youths generally in contexts of repression.